investigate the development of the olfactory organ and its histological structure of the amphibians Salamander Neurergus crocatus crocatus cope - Hane Hammode; Ismaeel Hasan; Shereen Qasim (College of Education for Pure Sciences, 2009)
ABSTRACT The present study is carried out to investigate the development of the olfactory organ and it`s histological structure in the embryos, Larvae and adults of urodele amphibians Salamander Neurergus crocatus crocatus cope. The study includes the morphology of the developmental stages at so the level of light microscope. The first sign of olfactory organ development in the Neurergus crocatus crocatus was the appearance of olfactory placode as one thickening on each side of the ectoderm opposite to prosencephalon at 28 stage. At early embryonic stages the olfactory placode appeared in the form of horse shoe. Progressively the olfactory pits appeared and become more deep. At late embryonic stage cells of olfactory placode more differentiated and appeared in multitypes. Some cells more packed and formed pyramids mass at the olfactory pit axis. The olfactory pit became V- shape. The axons of bipolar neurons differentiate, as well as the supporting cells and it's sensory tricheae well obvious. As the development progressed the two edges of olfactory pit approximate to each other anteriorly. While at the embryonic stage 39 the olfactory sac appeared. In addition the internal canal primordium of the external naris also differentiated. At the larval stage, the supporting spindle cells with their surface cilia well developed. In addition the main olfactory cavity differentiated as protruded chamber and several invagintions appeared in it's internal epithelium, as well as the vestibule and olfactory canal well developed. At stage 45 the vomeronasal organ differentiated as adiverticulum from the main olfactory cavity. The final larval stage characterized by the differentiation of receptor epithelium of vomeronasal organ and the olfactory organ flattened. At the olfactory organ of metamorphic stage the vistibule contacted with thick olfactory epithelium of the main olfactory cavity and the epithelium of cavity differentiate into serial transversed olfactory ridges with olfactory valleys in between. The number of ridge was 2 dorsally and 4 ventrally and appeared in radial pattern. In the adult mature stage several changes occurred, which include differentiation of protruded chamberes of main olfactory cavity, differentiation of vomeronasal organ the conduction of main olfactory cavity with external and internal naris. The vomeronasal epithelium extends to about 30% of the olfactory cavity, the large olfactory ridges decreased into miniridges and the cavity of lining epithelium appeared some- what smooth, the supporting ciliated cells were well obvious. The middle cavity of olfactory organ disappeared at all developmental stages.